2011
DOI: 10.1155/2011/608912
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the 2/3/5 Selective Positive Allosteric Modulators L-838,417 and TPA023 in Preclinical Models of Inflammatory and Neuropathic Pain

Abstract: GABAA receptors containing α2/3 subunits are current targets in the battle to develop new pain medications, as they are expressed in the spinal cord where increasing inhibitory drive should result in analgesia. However, this approach is prone to a range of side effects including sedation, cognitive impairment, and abuse as a consequence of the widespread influence of GABA. The ability to make subtype selective low-efficacy benzodiazepine compounds, which potentiate the action of GABA at specific α subunits, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 37 publications
4
31
1
Order By: Relevance
“…Moreover, in chronic constriction injury rats whereas tolerance develops to the antiallodynic actions of morphine after repeated administration, efficacy is maintained for L-838,417 after chronic treatment (Knabl et al, 2008). L-838,417 also attenuates high threshold mechanical activity of electrophysiologically identified spinal wide dynamic range neurones recorded from chronic constriction injury rats (Nickolls et al, 2011). Unfortunately, any effects of L-838,417 on spontaneous electrical activity of sensitized spinal dorsal horn neurones were not reported, as this might have provided useful information as the utility of subtypeselective GABA A receptor modulators to affect a surrogate marker of spontaneous pain, one of the most commonly reported clinical signs of chronic pain.…”
Section: Ns11394mentioning
confidence: 96%
See 2 more Smart Citations
“…Moreover, in chronic constriction injury rats whereas tolerance develops to the antiallodynic actions of morphine after repeated administration, efficacy is maintained for L-838,417 after chronic treatment (Knabl et al, 2008). L-838,417 also attenuates high threshold mechanical activity of electrophysiologically identified spinal wide dynamic range neurones recorded from chronic constriction injury rats (Nickolls et al, 2011). Unfortunately, any effects of L-838,417 on spontaneous electrical activity of sensitized spinal dorsal horn neurones were not reported, as this might have provided useful information as the utility of subtypeselective GABA A receptor modulators to affect a surrogate marker of spontaneous pain, one of the most commonly reported clinical signs of chronic pain.…”
Section: Ns11394mentioning
confidence: 96%
“…Although other subtype-selective GABA A receptor modulators have since been reported to possess similar analgesic properties in rodent models of pathological pain (Di Lio et al, 2011;Nickolls et al, 2011;Munro et al, 2011) little was known at this time about the efficacy profile required to mediate preferential analgesia. In pursuit of this goal NS11394 was compared to other known positive allosteric modulators (PAMs) that included the nonselective full allosteric modulator diazepam, the GABA A -α1-selective modulator zolpidem, the partial nonselective modulator bretazenil and the α4 preferring agonist gaboxadol .…”
Section: Ns11394mentioning
confidence: 99%
See 1 more Smart Citation
“…The analgesic effect in the formalin test was blocked by the benzodiazepine site antagonist flumazenil confirming that it occurred through GABA A Rs. L-838,417, which completely lacks intrinsic activity at α1-GABA A Rs and possesses partial agonistic activity at α2-, α3-, and α5-GABA A Rs (15-32%, relative to diazepam; McKernan et al, 2000), was tested in several rodent pain models where it was not sedative but active against inflammatory and neuropathic hyperalgesia (Knabl et al, 2008;Nickolls et al, 2011) and formalin-induced nociception (Hofmann et al, 2012). In addition, L-838,417 was active against hyperalgesia evoked by skin incision, a model of postoperative hyperalgesia (Reichl et al, 2012), and against capsaicin-induced central pain sensitization (Hansen et al, 2012).…”
Section: Antihyperalgesic Action Of Benzodiazepines With Improved Submentioning
confidence: 99%
“…Other benzodiazepines with low sedative propensities include HZ166 (Rivas et al, 2009) and TPA023 (Atack et al, 2006). HZ166, which exerts rather high intrinsic activity, was antihyperalgesic in inflammatory and neuropathic mouse models (Di Lio et al, 2011), while TPA023, which is a low intrinsic activity partial agonist, showed comparatively weak anti-allodynic or antihyperalgesic effects (Munro et al, 2011;Nickolls et al, 2011). Other compounds, which have higher intrinsic activities at α1-GABA A Rs than at α2-, α3-, and α5-GABA A Rs, did not exhibit antihyperalgesic activity at non-sedative doses.…”
Section: Antihyperalgesic Action Of Benzodiazepines With Improved Submentioning
confidence: 99%